Beyond lost earnings: The long-term impact of job displacement on workers' commuting behavior - Yige Duan; Oskar Jost; Ramona Jost (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
We study the long-term impact of job displacement on workers' commuting behavior. Our measures of commuting exploit geo-coordinates of workers' places of residence and places of work, from which we calculate the door-to-door commuting distance and commuting time. Using German employee-employer matched data and an event study design, we identify the causal effect of job loss on workers displaced during a mass layoff. Conditional on finding a new job, workers' commuting distance and commuting time rise sharply after displacement and gradually decline in subsequent years. The recovery is due to employer changes rather than migration, and a larger increase in commuting would mitigate the wage loss due to job displacement. To rationalize our findings, we build an on-the-job search model with heterogeneous firm productivity and commuting distances. Our model predicts a joint recovery of wages and commuting despite a static tradeoff between the two attributes. – – Wir analysieren den langfristigen Effekt von Entlassungen auf das Pendelverhalten von Beschäftigten. Hierfür nutzen wir Geoinformationen zum Wohn- und Arbeitsort der Beschäftigten, womit wir die Pendeldistanz und Pendelzeit bestimmen können. Mithilfe der zur Verfügung stehenden Betriebsinformationen und einer Ereignisstudie können wir zudem Massenentlassungen nutzen, um kausale Effekte auf Beschäftigte zu identifizieren. Unsere Ergebnisse zeigen, dass Beschäftigte, die wieder in Arbeit finden, deutlich erhöhte Pendeldistanzen und Pendelzeiten haben, welche in den Folgejahren abnehmen. Ferner zeigen unsere Ergebnisse, dass Beschäftigte, die nach einer Entlassung länger pendeln ihren Einkommensverlust reduzieren und die langfristige Erholung der Pendeldistanzen und Pendelzeit auf den Wechsel von Firmen zurückgeht und nicht durch Umzüge getrieben ist. Um unsere Ergebnisse analytisch zu diskutieren und zu begründen nutzen wir ein suchtheoretisches Modell, welches eine gemeinsame Erholung des Einkommens und Pendelns postuliert und damit eine statistische Betrachtung entscheidend erweitert.
Keywords: J3; J6; R23; R4; 330; commuting; mobility; displacement; job search